AI-Generated Writing Prompts to Foster Creativity, Autonomy, and Writing Skill Development in Online Language Learning - Nurfadila Nurfadila; Faiq Alıyev (Global Education : International Journal of Educational Sciences and Languages, 2024)
This study explores the impact of AI-generated writing prompts on students' creativity, autonomy, and writing skills in online language learning environments. Writer's block is a common issue in online education, affecting students’ ability to produce coherent and engaging written work. AI-generated prompts, such as those provided by GPT-4, are proposed as a tool to stimulate creativity and support autonomous learning. The study employs a quasi-experimental design involving [insert number] students, using pre- and post-test writing samples, surveys, and classroom observations to measure improvements in creativity, participation, and writing quality. The main findings show that students who used AI-generated prompts demonstrated significant improvements in writing quality, creativity, and engagement compared to those using traditional writing methods. The study concludes that AI prompts offer an effective method for enhancing students’ writing skills and fostering creativity in online language learning, but a balanced integration with traditional teaching methods is essential. Recommendations for educators include incorporating AI tools into writing instruction to promote creativity and support student autonomy. Future research should focus on the long-term effects of AI prompts and their application in diverse educational contexts.